2016
DOI: 10.1111/ceo.12849
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fibre layer thickness in a general population in Iran

Abstract: RNFL thickness in the 45 to 69-year-old Iranian population is lower compared to other studies. This difference should be noted in making disease diagnoses, particularly glaucoma. Also, there is a significant relationship between ageing and RNFL thinning in all quadrants. Longer axial length, myopia and male gender are associated with reduced RNFL thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…A point to consider is the difference in thinning rate which varies from 0.15 to 0.56 μ per year among different studies. 7 11 13 21 24 34 Age-related thinning rate of the overall pRNFLT in the present study (0.15 μ/per year) was similar to the studies with a wide age range (i.e., studies by Khawaja et al . [0.15 μ/per year] 24 and Parikh et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A point to consider is the difference in thinning rate which varies from 0.15 to 0.56 μ per year among different studies. 7 11 13 21 24 34 Age-related thinning rate of the overall pRNFLT in the present study (0.15 μ/per year) was similar to the studies with a wide age range (i.e., studies by Khawaja et al . [0.15 μ/per year] 24 and Parikh et al .…”
Section: Discussionsupporting
confidence: 90%
“… 6 Therefore, various population-based studies have examined the distribution of pRNFLT in different populations. 7 Accordingly, most OCT instruments are equipped with normative reference databases to facilitate clinical pRNFLT interpretation. However, most previous studies on pRNFLT distribution had a wide age range and were mostly related to Western or East Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the international standard RNFL database is not suitable for the application in the Chinese population, which may bring about a lot of missed diagnosis (taking the glaucoma as the normal one), or misdiagnosis (taking normal one as glaucoma) potentially, suggesting the need to establish Age is one of the important factors affecting the distribution of RNFL thickness, which has been confirmed in several studies. In the study conducted by Hashemi et al, the overall average RNFL thickness as well as the mean thickness of all quadrants went down dramatically with age, 49 while the decrease of RNFL thickness 8 25 was in connection with the ageing in other studies also. In addition to OCT studies, some studies have shown age-related RNFL thinning by histological analysis.…”
Section: Clinicalmentioning
confidence: 82%
“…However, these researchers did not find any relationship between gender and RNFL thickness, which corroborated the results of previous studies [ 23 ]. However, in recent years, a study conducted in Iran concluded that males tended to have thinner RNFLs than females [ 24 ]. A population-based study found that females had a smaller angle between the peak RNFL thickness of the superior-temporal and inferior-temporal sectors [ 25 ].…”
Section: Gendermentioning
confidence: 99%